2014
DOI: 10.1074/jbc.m113.528372
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-interacting Motifs Confer Full Catalytic Activity, but Not Ubiquitin Chain Substrate Specificity, to Deubiquitinating Enzyme USP37

Abstract: Background:The role of ubiquitin-interacting motifs (UIMs) in the deubiquitinating enzyme USP37 is unknown. Results: Inactivation of the UIMs in USP37 resulted in lower isopeptidase activity toward ubiquitin chains. Conclusion: The UIMs in USP37 are required for the full catalytic activity of the enzyme. Significance: This study reveals a novel mechanism to increase the catalytic activity of deubiquitinating enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
28
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 28 publications
9
28
3
Order By: Relevance
“…We identified USP37 as a novel interactor of HBx. Interestingly, in contrast to the earlier reports on nuclear distribution of USP37 [32] , we found that USP37 co-localized with HBx in the cytoplasm through a chaperoning mechanism. Many recent studies have highlighted the significant role of E3 ubiquitin ligases, deubiquitinases or substrate translocation between cell compartments, leading to substrate stability motivated us to explore the effect of HBx-driven exodus of USP37 from the nucleus vis-à-vis its intracellular stability.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We identified USP37 as a novel interactor of HBx. Interestingly, in contrast to the earlier reports on nuclear distribution of USP37 [32] , we found that USP37 co-localized with HBx in the cytoplasm through a chaperoning mechanism. Many recent studies have highlighted the significant role of E3 ubiquitin ligases, deubiquitinases or substrate translocation between cell compartments, leading to substrate stability motivated us to explore the effect of HBx-driven exodus of USP37 from the nucleus vis-à-vis its intracellular stability.…”
Section: Discussioncontrasting
confidence: 99%
“…USP37 has been reported previously to majorly localize in the nucleoplasm [32] . However, we observed that under HBx environment, USP37 translocated in the peri-nuclear-cytoplasmic region and co-localized with HBx (Pearson’s co-efficient of correlation = 0.994292; Mander’s co-efficient of correlation = 0.658119; n = 25).…”
Section: Resultsmentioning
confidence: 92%
“…S1E). As a control, the UIM region of USP37 equally pulled down Lys48- and Lys63-linked ubiquitin chains as reported22. Introduction of mutations into either UIM1 or UIM2 led to almost complete loss of binding to Lys48 ubiquitin chains, indicating that the tandem UIMs play a cooperative role in ubiquitin binding.…”
Section: Resultssupporting
confidence: 70%
“…Co-immunoprecipitation experiments in cells expressing the K48R or K63R mutant of ubiquitin demonstrated that USP25 binds more effectively to Lys48-, than to Lys63-, polyubiquitinated proteins also in the cell. Previous studies have shown that several UIMs, such as those in Hrs28, Rap802024, and Ankrd1321, bind to Lys63-linked ubiquitin chains specifically, while others, such as those in ataxin-3 7 and USP3722, bind to Lys48- and Lys63-linked chains with similar affinity. In contrast, reports of UIMs with binding specificity/preference to Lys48 ubiquitin chains have been limited.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the left panel of Figure 3G , endogenous 14-3-3γ was localized in both the cytoplasm and the nucleoplasm. However, the localization of 14-3-3γ was altered in the nucleus when USP37 was overexpressed, showing co-localization (Figure 3G , right panel) [ 24 , 25 ]. As the sequences of 14-3-3 isoforms are similar, we investigated whether the other six known isoforms of 14-3-3 interacted with USP37.…”
Section: Resultsmentioning
confidence: 99%